Desain Institusional Dewan Kehormatan Penyelenggara Pemilu (DKPP) Sebagai Peradilan Etik - M. Lutfi Chakim (The Constitutional Court of the Republic of Indonesia, 2014)
Ethics basically teach and emphasize to every individual including the organizer of election to take a stand and ensure that any action taken always relying on moral values. Ethics is an important element that must be adhered to every organizer of election, because it is one of the fundamental aspects for realizing democratic elections. Therefore, to enforce the Code of Ethic organizer of election, then formed Honorary Board of Organizer of Elections (DKPP) which aims to maintain independence, integrity and credibility of the Election Commission (KPU) and the Election Supervisory Body (Bawaslu) that is certainly going well and correctly. DKPP is an institution designed as a court of ethics, applying an open model and applying all the principles as in a court. So, for the organizer of election found to have violated the Code of Ethics, DKPP can provide sanctions in accordance with the level of the offense, that consists of a written reprimand, dismissal meantime, and permanent dismissal. Moreover DKPP decision is final and binding.